Development of the approach to modelling of the destructive catalytic hydroprocesses of atmospheric and vacuum distillates conversion; Catalytic Hydroprocessing In Oil Refining (STS-HydroCat - 2021) - Belinskaya N. S. Natalia Sergeevna; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Vymyatnin E. K. Evgeny Konstantinovich; Mauzhigunova E. N. Ekaterina Nikolaevna (2021, 2021)
Title screen